2019
DOI: 10.1177/0885328218824759
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized extracellular matrix microparticles seeded with bone marrow mesenchymal stromal cells for the treatment of full-thickness cutaneous wounds

Abstract: Extracellular matrix materials mechanically dissociated into submillimeter particles have a larger surface area than sheet materials and enhanced cellular attachment. Decellularized porcine mesothelial extracellular matrix microparticles were seeded with bone marrow-derived mesenchymal stromal cells and cultured in a rotating bioreactor. The mesenchymal stromal cells attached and grew to confluency on the microparticles. The cell-seeded microparticles were then encapsulated in varying concentrations of fibrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(40 reference statements)
0
9
1
Order By: Relevance
“…In contrast, Westman et al demonstrated that microparticles of decellularized tissues have the potential for cell delivery and paracrine therapy in the conditions of impaired regeneration [33]. A possible reason for the difference between the results obtained in this work and a number of results described in publications [33,34] may be the peculiarities of the mechanical properties and density of the studied tissues -in the examples, soft tissues are used, while this study used dense cartilage. Note that the effect of microparticles of cartilage in vivo on the stimulation of regeneration in degenerative diseases, such as OA, has not been previously studied, and only cases of implantation of MSCs with DPC in surgically created defects have been described [35,36].…”
Section: Stimulating Cartilage Regeneration In An Adjuvant Model Of Rabbit Knee Osteoarthritis Evolving Into Osteoarthrosiscontrasting
confidence: 65%
See 1 more Smart Citation
“…In contrast, Westman et al demonstrated that microparticles of decellularized tissues have the potential for cell delivery and paracrine therapy in the conditions of impaired regeneration [33]. A possible reason for the difference between the results obtained in this work and a number of results described in publications [33,34] may be the peculiarities of the mechanical properties and density of the studied tissues -in the examples, soft tissues are used, while this study used dense cartilage. Note that the effect of microparticles of cartilage in vivo on the stimulation of regeneration in degenerative diseases, such as OA, has not been previously studied, and only cases of implantation of MSCs with DPC in surgically created defects have been described [35,36].…”
Section: Stimulating Cartilage Regeneration In An Adjuvant Model Of Rabbit Knee Osteoarthritis Evolving Into Osteoarthrosiscontrasting
confidence: 65%
“…At the same time, it was shown that microparticles induce macrophages to proinflammatory (M1) polarization, and the gel obtained from the ECM polarizes macrophages to the regulatory/anti-inflammatory (M2) phenotype [32]. In contrast, Westman et al demonstrated that microparticles of decellularized tissues have the potential for cell delivery and paracrine therapy in the conditions of impaired regeneration [33]. A possible reason for the difference between the results obtained in this work and a number of results described in publications [33,34] may be the peculiarities of the mechanical properties and density of the studied tissues -in the examples, soft tissues are used, while this study used dense cartilage.…”
Section: Stimulating Cartilage Regeneration In An Adjuvant Model Of Rabbit Knee Osteoarthritis Evolving Into Osteoarthrosismentioning
confidence: 99%
“…Other commonly used materials in generating microparticles include inorganic polymers (hydroxyapatite, calcium phosphate), 142,143 organic polymers (poly-lactic-co-glycolic acid, poly-lactic acid, and poly-ethylene glycol), [144][145][146] natural proteins (collagen, ECM, and gelatin), 95,147,148 and polysaccharides (alginate, chitosan). [148][149][150] The use of these materials for the generation of microparticles have their own advantages and drawbacks. For instance, hydroxyapatite-based microparticles have been widely used for bone regeneration for its natural osteoinductive capacity.…”
Section: Fabrication Of Gelatin Nano and Microparticlesmentioning
confidence: 99%
“…At the same time, it was shown that microparticles induce macrophages to proinflammatory (M1) polarization, and the gel obtained from the ECM polarizes macrophages to the regulatory/anti-inflammatory (M2) phenotype [ 31 ]. In contrast, Westman et al demonstrated that microparticles of decellularized tissues have the potential for cell delivery and paracrine therapy in the conditions of impaired regeneration [ 32 ]. A possible reason for the difference between the results obtained in this work and a number of results described in publications [ 32 , 33 ] may be the peculiarities of the mechanical properties and density of the studied tissues—in the examples, soft tissues are used, while this study used dense cartilage.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Westman et al demonstrated that microparticles of decellularized tissues have the potential for cell delivery and paracrine therapy in the conditions of impaired regeneration [ 32 ]. A possible reason for the difference between the results obtained in this work and a number of results described in publications [ 32 , 33 ] may be the peculiarities of the mechanical properties and density of the studied tissues—in the examples, soft tissues are used, while this study used dense cartilage. Note that the effect of microparticles of cartilage in vivo on the stimulation of regeneration in degenerative diseases, such as OA, has not been previously studied, and only cases of implantation of MSCs with DPC in surgically created defects have been described [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%